Systematic Literature Review: Management Of Agricultural Land Transfer In Indonesia - Hadi Yuntarto; Nur Wening (Maneggio, 2026)
Agricultural land conversion in Indonesia continues to accelerate, threatening national food security, environmental sustainability, and the socio-economic stability of rural communities. This study examines the drivers, impacts, and control strategies of agricultural land conversion through a Systematic Literature Review of Scopus-indexed articles published between 2020 and 2025, retrieved using Harzing's Publish or Perish with the Crossref database. From an initial pool of one thousand articles, the screening and quality-assessment process yielded twenty-six articles for thematic analysis. The findings show that economic pressure, expansion of settlements and industry, urbanization, infrastructure development, and weak governance are the principal drivers of land conversion, producing impacts that include the loss of productive farmland, threats to food security, shifts in land tenure, and environmental degradation. Applying Fred R. David's strategic management framework reveals that strategy formulation rests on an adequate regulatory foundation, whereas implementation and evaluation remain weak due to fragmented inter-agency coordination, limited economic incentives for farmers, and the absence of an integrated One Map and real-time monitoring system. The novelty of this study lies in integrating SLR thematic synthesis with SWOT analysis and David's formulation-implementation-evaluation stages, a combination rarely applied explicitly to farmland-conversion research in Indonesia. The policy implications emphasize strengthening technology-based spatial governance, harmonizing cross-sector policy, and improving farmer welfare through stronger agricultural value chains to sustain long-term farmland protection..